Cytomegalovirus reactivation in mechanically ventilated patients with or without SARS-CoV-2 infection: A retrospective cohort study - Octave Cannac; Vanessa Pauly; Christine Zandotti; Léa Luciani; Paul-Rémi Petit; Xavier de Lamballerie; Rémi Charrel; Laurent Papazian; Damien Barrau; Geoffray Agard; Sami Hraiech (PLoS ONE, 2025)
Background Data comparing the incidence, risk factors and outcomes of cytomegalovirus (CMV) reactivation in SARS-CoV-2 positive and negative patients remain controversial. Design A retrospective cohort study in a tertiary center. Patients Patients admitted to the intensive care unit between December 2019 and May 2021, under invasive mechanical ventilation for 4 days or more and screened for CMV reactivation were included. Measurements The primary outcome was the incidence of CMV reactivation in SARS-CoV-2 negative and positive patients. Secondary outcomes included risk factors for CMV reactivation in both populations and survival analysis according to CMV reactivation in SARS-CoV-2 negative and positive patients. Results CMV reactivation occurred in 34.7% (n = 51/147) of SARS-CoV-2 negative patients and in 45.4% (83/183) of SARS-CoV-2 positive patients ( p = 0.08). When considering competing factors, SARS-CoV-2 infection was not associated with CMV reactivation (sub-hazard ratio (SHR) = 1.01 [0.68–1.49], p = 0.98). Treatment with methylprednisolone was significantly associated with CMV reactivation in the unadjusted and adjusted analysis (SHR 2.81 [2.01–3.93] p < 0.001; SHR 2.84 [1.94–4.15] p < 0.001 respectively). Patients combining SARS-CoV-2 infection and CMV reactivation had a significantly higher all-cause mortality. Among patients presenting a CMV reactivation, the administration of ganciclovir was a protective factor for day-60 mortality (HR = 0.4; [0.22–0.74] p = 0.004). Conclusion In this large retrospective cohort, CMV reactivation was not significantly associated with SARS-CoV-2 infection in patients undergoing invasive mechanical ventilation for at least 4 days. The major risk factor for CMV reactivation was treatment with methylprednisolone. The combination of CMV reactivation with SARS-CoV-2 infection was associated with a higher mortality whereas ganciclovir treatment reduced mortality.